A highly sensitive fluorescent 1, 8‐naphthalimide Schiff base probe for detection of Hg2+. Issue 6 (13th May 2022) - Shen, Qinqin; Kong, Xiaoxia; Li, Kaiyi; Wan, Tiantian; Dong, Jianping; Wu, Huilu
Abstract: A highly sensitive fluorescence "turn‐on" 1, 8‐naphthalimide Schiff base probe: N ‐allyl‐4‐(ethylenediamine‐salicylidene)‐1, 8‐naphthalimide (HL) for Hg 2+ was designed, synthesized and characterized. In addition, the sensing behavior of HL towards various transition metal ions has been investigated in solution (DMF/Tris–HCl buffer, 1:1, vol/vol, pH = 7.2). The HL exhibited high selectivity for Hg 2+ over other metal ions with obvious fluorescence enhancement. Moreover, the fluorescence intensity of HL showed good linearity with a correlation coefficient ( R 2 ) of 0.99, confirming that HL could be applied to detect the quantification of Hg 2+ in a linear fashion from 0.5 to 4 μM and the detection limit reach at 0.16 μM. Meanwhile, the association constant (Ka) between Hg 2+ and HL achieves 1.23 × 10 12  M −1 . Moreover, the fluorescence titration experiment and Job plot analysis indicate the formation of a 2:1 stoichiometric complex of HL with Hg 2+ . The fluorescence enhancement of HL response to Hg 2+ ions could be attributed to the photoinduced electron transfer (PET) mechanism. Abstract : A highly sensitive fluorescence "turn‐on" 1, 8‐naphthalimide Schiff base probe: N ‐allyl‐4‐(ethylenediamine‐salicylidene)‐1, 8‐naphthalimide (HL) for Hg 2+ was designed, synthesized, and characterized. HL showed an unrivaled sensing behavior and selectivity towards Hg 2+ over other competitive metal ions tested in solution (DMF/Tris‐HCl buffer, 1:1, vol/vol, pH = 7.2). The fluorescence enhancement of HL response to Hg 2+ ions could be attributed to the photoinduced electron transfer (PET) mechanism.